(untitled) (Journal of Student Affairs in Africa, 2021)
Since the dismantling of apartheid in South Africa, increasing numbers of black studentshave been enrolling at historically whites-only universities. This situation has beenparalleled by a resurgence of racialising discourses that represent black students as lackingin competencies, lowering academic standards and undeserving of their places at university.This paper investigates the impact of these discourses on black students at the Universityof Cape Town (UCT). Over six months, 24 students from seven departments and fourfaculties participated in a Photovoice project during which they produced photographsand stories representing their experiences at UCT. The findings demonstrate that, throughpractices of material and symbolic exclusion, racialising discourses of transformation hada detrimental impact on students, affecting their self-esteem, sense of belonging, andacademic performance. The discussion reflects on the identity dynamics and the copingstrategies that black students adopt to fit into the whiteness of the university.